Students’ Views on the Use of Technology in Geography Course - Nurbol, Ussenov; Kairat, Zhoya; Bakhadurkhan Аbdimanapov; Marat, Mamadiyarov; Kenjekey, Tleubergenova; Ussenova, Malika (International Journal of Emerging Technologies in Learning (iJET), 2020)
Use of technology in education enables students to be motivated and eager to participate in the lesson and is also a more effective tool in increasing motivation, encouraging students to the lesson and understanding the sub-ject. The aim of this study is to determine the views of secondary school students on the use of technology in geography lessons. Qualitative re-search method was used in this study. Semi-structured interviews were car-ried out with 32 students who took geography lessons in Kazakhstan dur-ing the 2018-2019 academic year. The semi-structured interview form de-veloped within the scope of this research was used as a data collection tool. Results of the study showed that secondary school students found tech-nology effective and funny to use in geography lessons. Projections, com-puters, tablets and smart phones were specified by the students as useful technological tools for teaching geography. Results of the study were dis-cussed with relevant literature and important implications for further re-search and practices were presented.